In vitro and in vivo accumulation of magnetic nanoporous silica nanoparticles on implant materials with different magnetic properties - Hilke Catherina Janßen; Dawid Peter Warwas; David Dahlhaus; Jessica Meißner; Piriya Taptimthong; Manfred Kietzmann; Peter Behrens; Janin Reifenrath; Nina Angrisani (Journal of Nanobiotechnology, 2018)
Abstract Background In orthopedic surgery, implant-associated infections are still a major problem. For the improvement of the selective therapy in the infection area, magnetic nanoparticles as drug carriers are promising when used in combination with magnetizable implants and an externally applied magnetic field. These implants principally increase the strength of the magnetic field resulting in an enhanced accumulation of the drug loaded particles in the target area and therewith a reduction of the needed amount and the risk of undesirable side effects. In the present study magnetic nanoporous silica core–shell nanoparticles, modified with fluorophores (fluorescein isothiocyanate/FITC or rhodamine B isothiocyanate/RITC) and poly(ethylene glycol) (PEG), were used in combination with metallic plates of different magnetic properties and with a magnetic field. In vitro and in vivo experiments were performed to investigate particle accumulation and retention and their biocompatibility. Results Spherical magnetic silica core–shell nanoparticles with reproducible superparamagnetic behavior and high porosity were synthesized. Based on in vitro proliferation and viability tests the modification with organic fluorophores and PEG led to highly biocompatible fluorescent particles, and good dispersibility. In a circular tube system martensitic steel 1.4112 showed superior accumulation and retention of the magnetic particles in comparison to ferritic steel 1.4521 and a Ti90Al6V4 control. In vivo tests in a mouse model where the nanoparticles were injected subcutaneously showed the good biocompatibility of the magnetic silica nanoparticles and their accumulation on the surface of a metallic plate, which had been implanted before, and in the surrounding tissue. Conclusion With their superparamagnetic properties and their high porosity, multifunctional magnetic nanoporous silica nanoparticles are ideal candidates as drug carriers. In combination with their good biocompatibility in vitro, they have ideal properties for an implant directed magnetic drug targeting. Missing adverse clinical and histological effects proved the good biocompatibility in vivo. Accumulation and retention of the nanoparticles could be influenced by the magnetic properties of the implanted plates; a remanent martensitic steel plate significantly improved both values in vitro. Therefore, the use of magnetizable implant materials in combination with the magnetic nanoparticles has promising potential for the selective treatment of implant-associated infections.